Nanostructured Materials Fabrication to Applications - Singh Seehra, Mohindar (IntechOpen, 2017)
There continues to be a worldwide interest in the size-dependent properties of nanostructured materials and their applications in many diverse fields such as catalysis, sensors, energy conversion processes, and biomedicine to name a few. The eleven chapters of this book written by different researchers include four chapters on the different methods of fabrication of specific materials followed by characterization of their properties, and the remaining seven chapters focusing on the fabrications and applications including three chapters on biomedical applications, two chapters on sensors, one chapter on solar cells, and one chapter on the use of nanoparticles in herbicides. These chapters provide up-to-date reviews useful for current and future researchers in these specific areas.